2013
DOI: 10.1186/1550-2783-10-48
|View full text |Cite
|
Sign up to set email alerts
|

Undenatured type II collagen (UC-II®) for joint support: a randomized, double-blind, placebo-controlled study in healthy volunteers

Abstract: BackgroundUC-II contains a patented form of undenatured type II collagen derived from chicken sternum. Previous preclinical and clinical studies support the safety and efficacy of UC-II in modulating joint discomfort in osteoarthritis and rheumatoid arthritis. The purpose of this study was to assess the efficacy and tolerability of UC-II in moderating joint function and joint pain due to strenuous exercise in healthy subjects.MethodsThis randomized, double-blind, placebo-controlled study was conducted in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 55 publications
1
57
0
9
Order By: Relevance
“…UC-II was reported to show intact tertiary and quaternary glycoprotein integrity, which allows the epitope recognition and hypo-responsive immune stimulation, whereas the denatured type II collagen contains no tertiary or quaternary glycoprotein integrity (Figure 3) [49]. Additionally, it has been mostly derived from chicken sternum as 40 mg of UC-II material that provides 10.4 ± 1.3 mg of native type II collagen, which was encapsulated an opaque capsule with excipients [75]. A combination of radiology and histology techniques demonstrated that treatment with UC-II limits the size of the osteophytes and potentially supports the mobility and functionality of joints [17].…”
Section: Uc-ii Safety Efficacy and Adverse Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…UC-II was reported to show intact tertiary and quaternary glycoprotein integrity, which allows the epitope recognition and hypo-responsive immune stimulation, whereas the denatured type II collagen contains no tertiary or quaternary glycoprotein integrity (Figure 3) [49]. Additionally, it has been mostly derived from chicken sternum as 40 mg of UC-II material that provides 10.4 ± 1.3 mg of native type II collagen, which was encapsulated an opaque capsule with excipients [75]. A combination of radiology and histology techniques demonstrated that treatment with UC-II limits the size of the osteophytes and potentially supports the mobility and functionality of joints [17].…”
Section: Uc-ii Safety Efficacy and Adverse Effectsmentioning
confidence: 99%
“…Animals 2020, 10, 697 18 of 24 UC-II involved the undenatured native chicken type II collagen (collagen 263.0 mg/g, hydroxyproline 32.9 mg/g), which was produced from chicken sternum cartilage in a GMP-certified facility via a patented, low-temperature manufacturing process that ensured a specific level of UC-II collagen [17]. In a recent letter, the novel faster-produced commercially available UC-II ® ingredient was reported to be identical with the material used in the previously published clinical research [75,76,119]. Several undenatured type II collagen, including UC-II ® , is a patented form of collagen with undenatured type II collagen for joint health support.…”
Section: Uc-ii Safety Efficacy and Adverse Effectsmentioning
confidence: 99%
“…An extensive review is available describing actual nutritional resources for osteoarthritis in general population [Lopez, b]. Among those accounting data in support to safeness and beneficial effects on osteoarthritis, there are: eicosapentaenoic + decosahexaenoic acid (polyunsaturated fatty acids ‐ PUFA) 2–4 g/day, γ‐linolenic acid 0.5–2 g/day, glucosamine 2 mg/kg/day, chondroitin 1.2 g/die, hyaluronan 50–100 mg/day, avocado‐saybean saponifiable fraction (ASU) 300–600 mg/day, S‐adenosylmethionine 400–600 mg twice/day, MSM (an organic sulfur donor nutrient) 1–3 g twice/day, phytoflavonoids/polyphenols 150–1,000 mg twice/day, probiotics/prebiotics 1–6 billion CFU/day, vitamin C 250 mg twice/day, vitamin E 200 IU/day, vitamin D3 1,000–4,000 IU/day, vitamin K2 0.5–1 mg/day, selenium 200–400 µg/day, manganese 5–10 mg/day, boron 6–8 mg/day and zinc 25–50 mg/day, as well as undenatured type II collagen (40 mg/day) [Lugo et al, ].…”
Section: Nutritional Aspectsmentioning
confidence: 99%
“…UC-II is derived from chicken sternum cartilage and is being marketed as a powdered, shelf-stable ingredient that at daily dose of 40 mg demonstrated clinical benefit by improving joint comfort, flexibility and mobility in OA patients. 20,21 Commonly used method to induce OA in rodents is unilateral medial meniscal tear (MMT) method resulting in rapid progression of degenerative changes in the articular cartilage of the medial tibial plateau including fibrillation of articular cartilage, osteophyte formation and a loss of chondrocytes 22,23 . The medial meniscotibial ligament anchors the medial meniscus to the medial tibial plateau to ensure high congruency between articular structures and the transfer of weight-bearing loads during locomotion.…”
Section: Introductionmentioning
confidence: 99%